(3GdCYQGVs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO SHb dfG bHd cJGHfG gPG JSYI hNeShf cJGHG hcJGHfG gPG SJhf cJGHG s
(3BNQgG (B:s
(3aJHGQc Gddg CMSf GdNGdbjf dG Edg EdG Gddg SHMGfc JYGdjJ YeG jbhd GdeHWdhf s
(3Vef eLehY , JQJjHgG (B: 60s
(3hQOJ CjVkG ai Qbe (B96 (3hgh GdebGdI GdSJhf ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B99 s
Keywords: (3GdcjejGA h GdWHjYjGJs